Schindler's list [videorecording (DVD)] - Zaillian, Steven; Neeson, Liam; Kingsley, Ben, 1943-; Fiennes, Ralph; Keneally, Thomas (Universal Studios Home Entertainment, 2013)
The incredible true story follows the enigmatic Oskar Schindler, who saved the lives of more than 1,100 Jews during the Holocaust. It is the triumph of one man who made a difference and the drama of those who survived one of the darkest chapters in human history because of what he did.